ANALYSIS OF THE SEASONALITY OF ADMISSIONS DUE TO RESPIRATORY CAUSES IN THE PEDIATRIC EMERGENCY ROOM: AN EXPERIENCE REPORT - Antunes, Michele; Silva, Thaiane Vaz; Matiello, Fernanda Ramos; Ramos, Amaranta Rangel (Seven Editora, 2026)
INTRODUCTION: Respiratory diseases account for a significant portion of admissions to the pediatric emergency room and exhibit seasonality with an increase in the fall-winter period. Understanding this dynamic supports the planning of beds, staff, and supplies, as well as patient safety during periods of higher demand. OBJECTIVE: To describe, based on an experience report, the analysis of the seasonality of admissions due to respiratory causes between January 2023 and July 2025. METHOD: This is an experience report, developed in the Pediatric Emergency Department of a tertiary general hospital, covering January 2023 to July 2025. Aggregated institutional data (monthly spreadsheets, reports, indicators) were analyzed using descriptive statistics and integrated into a narrative analysis of the experience. RESULTS: Consistent seasonality was observed: low at the beginning of the year, rising since March, and concentrated in the fall-winter period. In 2023, there were 420 admissions, with a plateau between May and September. In 2024, there were 394 admissions (-6.2% vs. 2023), with a peak in May (55) and a second peak in October (52). In 2025 (Jan-Jul), there were a total of 175 admissions (-30.0% vs. 2023; -17.8% vs. 2024 for the same period), culminating in a peak in July (55). The temporal concentration was 63.8% of the 2023 admissions in May-September; 48.7% in 2024; and 78.3% of the first half of 2025 in May-July. FINAL CONSIDERATIONS: The seasonal pattern and interannual variations demand seasonal planning with staggered availability starting in April and peak availability between June and July. Continuous monitoring of indicators is necessary to mitigate overload and improve outcomes.